The Child Language Teacher - Anitha Pandey (My University, 2012)
This book is The Child Language Teacher consists of 10 Units on learning about Language and Literacy: Youngsters at the Helm, Collaborative Continuity: Linguistic Evidence, Background Research, Key Concepts and Misconceptions, Research Framework and Analysis, Teaching Families of Learners: Multi-age and Multilevel Language-Literacy Acquisition, How My Mother Learned English, Enhancing Communication for Individuals with Huntington's Disease: A Child Facilitated Approach, Constantly Communicating: From Architect and Olympian to Strategic Communicator and Conclusions.
Keywords: English